The Influence of Basic Life Support Education Increases The Knowledge And Atitudes Of The Pemulutan Community - Septi Ardianty; Sutrisno (Jurnal Inspirasi Kesehatan, 2023)
Introduction: Cardiac arrest or respiratory arrest is a life-threatening problem and can result in death if it takes too long to be helped (Ministry of Health, 2016) .The increasing cases of cardiac arrest in the community certainly raises serious new problems, namely disability to death that should be able to prevented by anyone who was in the environment of the incident, including one of the people. The solution that can be done is to provide education about basic life support (BLS) to the community . Research related to the influence of education about BLS on knowledge and attitudes of the community has not been widely carried out in the province of South Sumatra. Purpose: To find out the effect of basic life support education on the knowledge and attitudes of the pemulant community. Method: This research is a quantitative study using a pre-experiment, with a pre-test and post-test design. The population in this study was the productive age community in the Pemulutan subdistrict, totaling 240 respondents and the research sample totaling 33 respondents, the sampling technique used consecutive sampling . The research was conducted from February to April 2023. Data collection techniques used knowledge and attitude questionnaires before and after BLS education . Data analysis carried out through 2 stages , namely descriptive analysis and inferential analysis using the Wilcoxon test . Results: The results of this study indicate that the average value of prior knowledge is 12.88 and after the average value of knowledge is 18.83 with ρ value= 0.001. The average value of the attitude before 45.50 and the average value of the attitude after 55.43 with ρ value= 0.001. Discussion: Knowledge and attitudes increased after being given education, there was a significance of Basic Life Support education on the level of knowledge and attitudes.